SIMULASI NETWORK REFERENCE MODEL PADA JARINGAN WIMAX - Barokatun Hasanah; Muhamad Komarudin; - - Herlinawati (Jurnal Informatika dan Teknik Elektro Terapan, 2013)
Abstract WiMAX Forum has introduced a logical representation for WiMAX network architecture known as the Network Reference Model. NRM (Network Reference Model) has the function of an entity and reference point where the function is defined interoperability between these entities function. An NRM also defines the reference point that connects R1 to R8 entity functions. The research was conducted by simulating the reference point R1 to R8 that exist in NRM using the software simulator. The design of the network is done by making two scenario are used to represent a reference point. Two scenario using a single ASN-Gateway dan two ASN-Gateway.Key Words: WiMAX, Network Reference Model, reference point